Pre-emptive and preventive NSAIDs for postoperative pain in adults undergoing all types of surgery (Protocol) - Doleman, Brett; Leonardi-Bee, Jo; Heinink, Thomas P.; Lund, Jon; Williams, John P. (Wiley, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: